Selective Sampling of Empirical Settings in Organizational Studies - Denrell, J; Kovacs, B (2008)
Most studies in organization theory are retrospective and rely on historical data. Because more data are available about widely diffused practices or about large populations, studies typically focus on these. Using simulation, we demonstrate that such selective sampling of empirical settings has important implications for two major research programs in organization theory. Diffusion researchers typically study practices that have diffused widely. We show that this implies that they will underestimate contagion effects. Researchers in organizational ecology often study populations that have become large. We show that such selective sampling of populations can generate spurious non-monotonic density dependence. We discuss the implications of such selective sampling of empirical settings and suggest ways to correct for the bias.